2018
DOI: 10.2215/cjn.01750218
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells and Kidney Transplantation

Abstract: The ability of the immune system to differentiate self from nonself is critical in determining the immune response to antigens expressed on transplanted tissue. Even with conventional immunosuppression, acceptance of the allograft is an active process often determined by the presence of regulatory T cells (Tregs). Tregs classically are CD4 cells that constitutively express high levels of the IL-2 receptor chain CD25, along with the transcription factor Foxp3. The use of Tregs in the field of solid organ transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…Regulatory T cells in the draining lymph node have been shown to be critically important for corneal allograft survival ( 35 , 36 ) and depletion of these cells negatively impacts the survival of the graft ( 37 ). Indeed, several groups have shown that adoptive transfer of regulatory T cells and other in vivo strategies to increase the numbers of regulatory T cells can have beneficial effects on transplant survival ( 5 , 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T cells in the draining lymph node have been shown to be critically important for corneal allograft survival ( 35 , 36 ) and depletion of these cells negatively impacts the survival of the graft ( 37 ). Indeed, several groups have shown that adoptive transfer of regulatory T cells and other in vivo strategies to increase the numbers of regulatory T cells can have beneficial effects on transplant survival ( 5 , 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy with transplanted Treg cells has been used in autoimmune diseases and other immune-associated diseases, including type-1 diabetes mellitus, systemic lupus erythematosus (SLE) and graft vs. host disease (GVHD) (713). Culturing sufficient numbers of Treg cells in vitro is the foundation of Treg-based immunotherapy, and maintaining the stable inhibitory function of Treg cells in vivo is pivotal for successful treatment (8,9). However, the stability and inhibitory function of Treg cells in the internal inflammatory environment requires further systematic investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Co-expression analysis of the expression levels of immune cells obtained in this study showed that the correlation between T cells regulatory (Tregs) [10][11][12][13]and Neutrophils [14][15][16][17] was the strongest, with a coe cient of 0.78, and the two cells with the weakest correlation were Macrophages [18][19] and T cells follicular helper [20][21], the correlation coe cient is -0.59 (Figure 3). After obtaining the matrix of immune cells, we wondered whether these immune cells could distinguish between the normal group and the tumor group.…”
Section: Co-expression Analysis Between Immune Cellsmentioning
confidence: 77%